2017
DOI: 10.1016/j.actamat.2017.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of grain size and deformation temperature on hydrogen-enhanced vacancy formation in Ni alloys

Abstract: Positron annihilation spectroscopy and thermal desorption spectroscopy experiments were combined to ascertain the role of hydrogen on generation of vacancies and vacancy clusters in Ni alloys. The effects of grain size and deformation temperature are emphasized for pure Ni single crystals and polycrystalline Ni-201 alloy samples with two grain sizes that were thermally pre-charged with 3000 appm hydrogen. Variation in positron lifetime and intensity suggests that hydrogen enhances and stabilizes vacancies and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(22 citation statements)
references
References 42 publications
2
18
0
Order By: Relevance
“…The report [8] also mentions the effect of H atoms on the vacancy formation in deformed steel based on PAL measurement. Similar vacancy formation is also observed in tempered martensitic steels prestressed cyclically during H charging [9] , in Inconel 625, iron [10] , and nickel alloys [11] , which are deformed and H charged concurrently. In the report [11] , PAL is also used for estimating vacancy formation.…”
Section: Introductionsupporting
confidence: 68%
“…The report [8] also mentions the effect of H atoms on the vacancy formation in deformed steel based on PAL measurement. Similar vacancy formation is also observed in tempered martensitic steels prestressed cyclically during H charging [9] , in Inconel 625, iron [10] , and nickel alloys [11] , which are deformed and H charged concurrently. In the report [11] , PAL is also used for estimating vacancy formation.…”
Section: Introductionsupporting
confidence: 68%
“…Also this similarity suggested that, in the present work, this phenomenon was operative only during finale rupture, maybe for a critical strain level, since only the elongation to failure was modified by hydrogen during tensile tests. A recent work of Lawrence et al suggested that hydrogen enhanced vacancy clustering could induce an Orowan type hardening component, which is effective even when hydrogen is essentially immobile (at low temperature) and that mobile hydrogen (at high temperature) provided an additional hard ening increase by interacting with mobile dislocations to restrict dislocation cross slip [27]. Obviously, these specula tions are not available in the present work given that yield strength and work hardening are not affected by hydrogen.…”
Section: Resultsmentioning
confidence: 74%
“…A number of recent publications 5 9 have demonstrated that the key to further enhancing the mechanical performance requires engineering their nanostructures. The core concept of this new paradigm is to characterize extended defects including grain boundaries 10 , dislocations 11 , surfaces 12 , and interfaces 13 , as well as point defects such as interstitials 14 , substitutionals 15 , and vacancies 16 etc. Even more importantly, it is of special interest to understand how these defects interact and how such interactions trigger structural evolution such as nanoscale phase transformations 17 .…”
Section: Introductionmentioning
confidence: 99%